Peningkatan Keaktifan melalui Model Problem Solving pada Pembelajaran Tematik Kelas IV SD Muhammadiyah Siliran Kulon Progo - Rifka Marandani; Chairiyah; Atik Sri Lestari (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2021)
This study aims to describe the increase in the activity of fourth grade students of SD Muhammadiyah Siliran by using the Problem Solving learning model. The action hypothesis in this study is that the use of the Problem Solving Model can increase the activity of fourth grade students at SD Muhammadiyah Siliran. This research is a type of classroom action research (CAR). This research was conducted in two cycles, each cycle includes four stages, namely planning, implementation, observation, and reflection. Research setting in SD Muhammadiyah Siliran. The subjects of this study were all fourth grade students of SD Muhammadiyah Siliran, totaling 15 students.The object of this research is the use of the Problem Solving model in thematic learning to increase student activity.Data collection techniques using observation. The results showed that after applying the Problem Solving model in class IV, student activity increased. This shows an increase in the observation of student learning activities in the pre-cycle by 68.80%, an increase in the first cycle of 72.27%, and an increase in the second cycle of 85.07% The average student learning activity increased by 12.8% from cycle I to cycle II. Indicators of success have been achieved.